Perceptions on disabilities and illnesses in late Joseon Korea - Yoo, Hyun Jae (International Journal of Korean Humanities and Social Sciences, 2023)
This paper seeks to delineate and explain changing public perceptions towards those who suffered from deafness, blindness, or intellectual disability in Joseon Korea. In the fifteenth century, the Great Code of State Administration (경국대전, 經國大典 Gyeongguk Daejeon) prohibited discrimination against the disabled. The deaf and blind in particular even enjoyed favorable attention. The state provided such economic benefits as exemption from taxes as a way to compensate them for their impaired abilities, thereby fostering a rather favorable social climate towards persons with disabilities. Some blind persons were even believed to have such special talent as fortune telling. In the eighteenth century, however, negative perceptions towards the disabled began to gain strength. Increasing frequency of documented references to disability as an object of mockery suggests that the state and the society alike viewed the disabled as ‘useless people’ (폐인). Mainly utilizing court histories, literary anthologies, army rosters (군적), and military division (군영) records, this paper argues that overall change in the Joseon economy fueled discrimination against the disabled. In particular, changes in the military defense system and its associated military tax (군포) significantly contributed to the negative portrayal, as the new practice tended to divide the population into households collectively responsible for tax levies. By the nineteenth century, the state’s harsher treatment of the disabled set the stage for outright discrimination against disabled in modern Korea, exacerbated by the introduction of the Western notion of eugenics.